The tax treatment of commuting expenses and job-related mobility - Eike Baumgart; Kay Blaufus; Frank Hechtner (Arbeitskreis Quantitative Steuerlehre (arqus), 2023)
Amid global climate change concerns, policymakers worldwide are increasingly scrutinizing environmentally harmful subsidies. This study examines the tax-deductibility of job-related commuting expenses, which has faced criticism for promoting longer commutes and congestion. Through a controlled, randomized survey experiment, we confirm that the tax-deductibility of commuting expenses results in longer commutes but does so with minimal economic impact. Increasing the deduction rate by e0.10 leads to an average acceptance of 377-meter-longer commutes. Surprisingly, subjects are inattentive to changes in the tax deduction's size when such changes are presented as tax-deductible expenses rather than as direct cash effects. In contrast, abolishing the tax deductibility significantly reduces average commuting distances by nearly 9 percent. These findings highlight people's responsiveness to the mere presence of the commuter tax break while being less sensitive to its specific size. Policymakers should consider these findings when evaluating the effectiveness of such tax deductions in mitigating climate change or their economic efficiency effects.
Keywords: D90; H21; H24; J22; R23; R28; R41; 330; Commuting Behavior; Commuting Subsidies; Tax Policy; Tax Complexity; Rational Inattention